Review of the validity of scales to estimate age, growth, life history and maturity schedule of Hilsa shad Tenualosa ilisha(Hamilton, 1822) - Almukhtar, Mustafa A. (Iraqi Journal of Aquaculture, 2022)
This study reviewed the validity of using the scales of Hilsa Shad (Tenualosa ilisha) and other migratory species as a tool to estimate age, growth, maturity schedule and migration. Hilsa Shad scales were used long ago, and proved in several studies. most of these studies showed that scales could give valuable information, which could be used as benchmarks in the study of fisheries and plans for future successful management policies. Bt it needs Patience and precision for the extraction of these information, because of difficulties in reading these scales. The work need to study the sufficient number of scales and practice, to be easily. As a result, this study will open doors that were closed for decades to set new migration study tools for Hilsa Shad in Iraq.